Theory and practice of the organization of accounting of deferred tax assets and liabilities. (Journal of Economic Research & Business Administration, 2016)
The development of the capital markets has led to increase the requirements to the content and quality of the accounting information. One of the consequence of this process was the emergence of some indicators such as deferred tax assets and liabilities in the financial statements. The disclosure of the information of deferred tax assets and liabilities in financial statements allows users of the statements not only to receive the information about the current, but also about the future tax consequences of business transactions of commercial organizations. The value of information on deferred tax assets and liabilities lies in the fact that users of financial statements can determine the amount of net profit, calculated including future tax liabilities of commercial organizations. Large-scale reforms in the field of reforming the national accounting system , aimed towards the convergence of national accounting rules with International standards of financial accounting and reporting have led to the need for reporting the deferred tax assets and liabilities in our country.
Keywords: Accounting income; taxable income; corporate income tax; deferred tax assets; deferred tax liabilities.